The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.9738/intsurg-d-15-00043.1
|View full text |Cite
|
Sign up to set email alerts
|

Giant Splenic Artery Pseudoaneurysm: A Case Report and Literature Review

Abstract: Splenic artery aneurysms (SAAs) are the third most frequent intra-abdominal aneurysm, following abdominal aorta and iliac artery aneurysms. SAAs are classified according to their involvement of arterial wall layers: true aneurysms involve all 3 layers (intima, media, and adventitia), and pseudoaneurysms involve only one or two. Herein we present a new case of giant pseudo SAA. A 65-year-old female patient with a pancreatic mass and iron deficiency was referred to our clinic for further investigation. Abdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 17 publications
0
45
0
1
Order By: Relevance
“…Usually, at presentation SAA measures about 2.1cm and rarely presents with the diameter above 3.1cm. Giant aneurysms are generally defined as the diameter >5cm [1].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, at presentation SAA measures about 2.1cm and rarely presents with the diameter above 3.1cm. Giant aneurysms are generally defined as the diameter >5cm [1].…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Akbulut and Otan 18 reviewed 69 papers and reported that giant SAA with a diameter of >5 cm was associated with a mortality of 33.3% in ruptured cases. Another literature review by Yagmur et al 19 revealed that spontaneous rupture could be considered the most critical complication of splenic artery pseudoaneurysm. Therefore, the general consensus is that all splenic artery pseudoaneurysms and SAAs meeting the criteria should be treated to reduce the potentially lifethreating risk associated with rupture.…”
Section: Discussionmentioning
confidence: 99%
“…However, pseudoaneurysms more commonly manifest through silent anemia, melena, pain in the upper left quadrant, or copious bleeding followed by hemodynamic instability. 4 , 5 Therefore, a pseudoaneurysm should be considered a disease requiring emergency care that must be diagnosed and treated promptly and precisely. 9 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast, true aneurysms of the splenic artery account for more than half of all visceral artery aneurysms. 5 Risk factors for true splenic artery aneurysm are hypertension, atherosclerosis, cirrhosis, portal hypertension, liver transplantation, female sex, pregnancy, and multiparity, 6 but can also include splenomegaly, medial fibrodysplasia, arteritis, collagen vascular disease, polyarteritis nodosa, systemic lupus erythematosus, anomalous splenic artery origin, a 1-antitrypsin deficiency, and inflammatory and infectious diseases. 5 - 7 …”
Section: Introductionmentioning
confidence: 99%